Case study: the market is calling for Biolage R.A.W - Anes, Paulo Jorge Padrão (2018)
Which one of us never noticed the emerging trend of natural products? The presented case study aims to study the increasing demand for natural and organic cosmetics and how can Biolage R.A.W. leverage from it. Biolage R.A.W. is a natural professional haircare brand taking its first steps in the Portuguese market. The brand is already facing a lack of awareness which, alongside with the higher prices of its products can leave the brand more exposed. So, how can Biolage R.A.W. come up with a launch strategy to solve these main problems? To better understand the market and brand, an exhaustive qualitative and quantitative analysis was developed that allowed to draw some primary conclusions: Millennials are the healthy beauty products generation and are willing to pay more for natural products. Regarding the launch communication strategy, Biolage R.A.W should follow an integrated communication strategy, using different communication options, creating synergies, to obtain different outcomes in a more cost-efficient way. Taking into consideration millennials’ characteristics, online platforms and e-influencers should take a big part of the brands’ communication. Although recent in the market, Biolage R.A.W. can easily be aware of the growing demand for natural cosmetics and take it as an opportunity to develop and expand the brand. In this case study is clear that the brand has four large strategic core areas to develop, of which two are remarkable for their potential for expansion: distribution channels and innovation. The brand must in the future explore new distribution channels such as natural supermarkets and prioritize a brand extension at the product and category level by launching a line of natural dyes for the hair.